Pattens of human knowing in the information society: a philosophical study of the epistemological implications of the information revolution - Bigirimana, Stanislas (2011)
The aim of this thesis is to introduce a dynamic and integrative epistemology based on the notion of information. This thesis is mainly a critique of normative epistemology on the grounds that normative epistemology through its adoption of the assumptions of methods of modern sciences, models all processes of human knowing to the physical sciences and henceforth upholds a mechanical model of the universe which is indistinctly applied to natural phenomena and human behavioral and cognitive processes; (2) reduces human knowing to logical-deductive processes in the attempt to achieve a degree of certainty that is comparable to the one achieved by mathematics; (3) reduces knowing to achieving accurate representations of reality (true-justified-beliefs or clear and distinct ideas) with the assumption that the knower is a passive and impartial spectator of reality. The dynamic and integrative model of epistemology that this thesis advocates rejects the modeling of all processes of human knowing on the physical sciences basing itself on evidence from neurophysiology, cognitive and behavioral sciences. The knower is not a passive spectator of reality but an active agent who (1) is continuously in relation with his or her environment; and who (2) is involved processes of meaning and value creation as the knower pursues various goals. Dynamic and integrative epistemology defines knowing not in terms of achieving accurate representations (true-justified-beliefs or clear and distinct ideas) but as accumulating insights through information processing i.e. enriching the immediate data of experience with value and meaning for the purposes of decision-making and problem-solving. Dynamic and integrative epistemology is only possible in the context of a paradigm shift from mechanical (causal) to cybernetics (information processing) models. It overcomes the analysis and synthesis dichotomy characteristic of mechanical models and upholds systems thinking as a way of tackling in inherent complexity of reality. Dynamic and integrative epistemology rejects the reduction of wisdom to certainty or knowing to thinking that led to top-down logical deductive systems. It advocates a bottom-up approach that aims at wisdom in experiencing, understanding, judging and acting within the limits of a human “bounded rationality” i.e. subject to humanly attainable pre-determined goals (satisficing rather than optimizing), complexity of the subject matter and the limited human computational abilities. This is possible through processes that apply the methods of heuristics rather than clearly determined algorithms in processes that span at Lonergan’s four levels of consciousness (the empirical, the intellectual, the rational, the responsible) and that require attention, intelligence, reasonableness and responsibility as resources.
Keywords: Hochschulschrift; Lonergan, Bernard J. F.; Kybernetik; Informationsgesellschaft; Wissenschaftsphilosophie; Erkenntnistheorie